Fronto-parietal Osteomyelitis managed by Bipedicled Bucket Handle scalp flap - Dixit, Pawan K.; Upadhyay, Divya Narain (International Surgery Journal, 2018)
Osteomyelitis of skull is rare clinical entity in today’s world. Mortality from complications from skull osteomyelitis is 20-40 %. We report a 60-year-old patient presented with fronto-parietal osteomyelitis with orbital extension, with known cardiac and pulmonary disease. Large bipedicled bucket handle flap was used for soft tissue reconstruction. Though free flap reconstruction is ideal for large scalp defect, it requires technical expertise and patient’s fitness for surgery. Bipedicled bucket handle flap can be successfully used for large scalp defect reconstruction in patients in which free flap reconstruction is not possible.